The Influence of Inflation and Energy Subsidies on the Stability of the Rupiah Exchange Rate in Indonesia (2015-2024) - Septi Nurmalita; Eka Septariana Puspa; Surya Anugrah; Windy Permata Suyono; Deas Shaqilla Putri (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
This study examines the determinants of exchange rate stability in Indonesia during the period 2015-2024, focusing on the roles of inflation and energy subsidies. Using a quantitative explanatory approach and multiple linear regression analysis with annual time-series data, this research explores how these two macroeconomic variables influence the volatility of the Indonesian rupiah against the U.S. dollar. The results show that inflation does not significantly affect exchange rate stability, indicating that effective monetary policy by Bank Indonesia has successfully mitigated inflationary pressures on the currency. Meanwhile, energy subsidies are found to have a significant effect on exchange rate stability, implying that fiscal policy related to energy spending plays a crucial role in shaping the rupiah’s movement. Collectively, inflation and energy subsidies explain 49.1% of the variation in exchange rate stability. These findings highlight the importance of harmonizing fiscal and monetary policies to maintain macroeconomic resilience and strengthen the credibility of Indonesia’s exchange rate management.